Mycoplasmas as Host Pantropic and Specific Pathogens: Clinical Implications, Gene Transfer, Virulence Factors, and Future Perspectives - Dawood, Ali; Algharib, Samah Attia; Zhao, Gang; Zhu, Tingting; Qi, Mingpu; Delai, Kong; Hao, Zhiyu; Marawan, Marawan A.; Shirani, Ihsanullah; Guo, Aizhen (Frontiers in Cellular and Infection Microbiology, 2022)
Mycoplasmas as economically important and pantropic pathogens can cause similar clinical diseases in different hosts by eluding host defense and establishing their niches despite their limited metabolic capacities. Besides, enormous undiscovered virulence has a fundamental role in the pathogenesis of pathogenic mycoplasmas. On the other hand, they are host-specific pathogens with some highly pathogenic members that can colonize a vast number of habitats. Reshuffling mycoplasmas genetic information and evolving rapidly is a way to avoid their host’s immune system. However, currently, only a few control measures exist against some mycoplasmosis which are far from satisfaction. This review aimed to provide an updated insight into the state of mycoplasmas as pathogens by summarizing and analyzing the comprehensive progress, current challenge, and future perspectives of mycoplasmas. It covers clinical implications of mycoplasmas in humans and domestic and wild animals, virulence-related factors, the process of gene transfer and its crucial prospects, the current application and future perspectives of nanotechnology for diagnosing and curing mycoplasmosis, Mycoplasma vaccination, and protective immunity. Several questions remain unanswered and are recommended to pay close attention to. The findings would be helpful to develop new strategies for basic and applied research on mycoplasmas and facilitate the control of mycoplasmosis for humans and various species of animals.